The Culture of The Following of Melayu Identity in Indonesia - Sutikno, Sutikno (Research Collaboration Community (Rescollacom), 2021)
The diversity of ethnic groups makes Indonesia also has a lot of local culture, one of which is folklore. Part of the culture of a society that is spread and traditional in nature which is passed down orally and from generation to generation is also called folklore. Folklore consists of two big words, namely folk and lore. Folk means a group of people who have physical, social, and cultural identifiable characteristics so that they can be distinguished from other groups. This research is a culture-based research that investigates folk culture as the identity of the Malay Archipelago tribes in Indonesia. Folklore or in Indonesian commonly referred to as folklore, is a branch of science that reviews and discusses culture. Folklore consists of two syllables, namely folk and lore. The purpose of this study is to describe Malay folklore as the development of the identity of the Malay community. This research is a qualitative descriptive study with an analysis method (content analysis). This research describes, analyzes, interprets the data. The method of analysis is using the literary reception approach and hermeneutics. The literary reception approach is used to find out how readers respond to Nusantara Malay folklore in Indonesia. The results of the analysis based on folklore (folklore) of the Archipelago in Indonesia, obtained include 1. People who always act and behave correctly always win, 2. People who act and behave in the wrong way will eventually perish, 3. God can make any miracle so that it doesn't happen. nothing is impossible for Him, 4. People who are arrogant, arrogant and have bad intentions will get reinforcements according to their actions. 5. The poor and weak should not be insulted or excluded because by the power of God they can become strong. So it can be concluded that the notion of folklore is a human culture (collectively) which is passed down from generation to generation, both in oral form and in the form of gestures. In Indonesia itself, every region, ethnicity, group, tribe, and religious group of each society has developed its own folklore so that there are various kinds of folklore that exist in Indonesia